(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2024)
In recent years, artificial intelligence has deeply transformed various aspects of life, and education is no exception. Globally, teachers face the challenge of integrating tools like chatbots, specifically ChatGPT, into the teaching-learning process. These programs, capable of generating quick and accurate responses, provide a significant advantage for students by saving time in the search and analysis of information. However, this ease also presents challenges for educators, who must rethink their pedagogical strategies to avoid being supplanted by these technologies. This paper aims to analyze how artificial intelligence can be an ally in Social Sciences education at the secondary level, exploring both its benefits and limitations. Through concrete examples, it demonstrates how AI can diversify and enrich pedagogical approaches, transforming the way topics are addressed in the classroom.